Prinsip-prinsip Hukum Kelalaian Sebagai Penyebab Ganti Rugi dalam Hukum Ekonomi Syariah di Indonesia - Asyari Hasan; Alimin Alimin; Rizal Fahlefi; Desmadi Saharuddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This study discusses what are the concepts of legal principles of negligence as a cause of compensation contained in the positive Indonesian Islamic economic law concerning the implementation of contracts for Islamic financial institutions that are studied in a qualitative-normative exploratory manner. This study indicates that there are six legal principles of negligence as a cause of compensation in the positive law of Indonesian sharia economy, namely: 1) carried out with careful consideration, 2) carried out appropriately, 3) carried out carefully, 4) business activities may not exceed permitted limits, 5) business activities must be in line with the provisions stipulated in the contract (not violating the agreement), and 6) negligence classified as intentional negligence and accidental negligence. While the legal principles of negligence contained in conventional law are currently more complete (11 principles of negligence) than those contained in the positive law of sharia economy (only 6 principles)